The buyer: the making and breaking of an undercover detective - Thomas, Liam (Ebury Press, 2023)
Liam Thomas was an officer in the Met for over a decade, many of those years spent deep undercover at the heart of Britain's most dangerous criminal enterprises. But the murky world of covert operations teaches him that justice is far from black and white - and a family secret reveals that corruption is closer to home than he had ever expected. A thrilling memoir of a life lived amongst a world of corruption, justice and questionable loyalties, this book tells the real story of the police's line of duty